Relationship of History of Hypertension with Severity and Onset of Preeclampsia: A Cross-Sectional Study - Pramaningtyas, Miranti Dewi; Adnan, Muhammad Luthfi; Weningtyas, Vyanda Sri; Wahyana, Eka Budi (Indonesian Socety of Obstetrics and Gynecology, 2025)
Objective: This study aimed to find correlation between a history of hypertension with severity and onset of preeclampsia.Methods: A retrospective cohort study with retrospective analysis of medical record data in patients with preeclampsia and severe preeclampsia from November 2021 – February 2022 was conducted at dr. Soediran Mangun Sumarso Regional General Public Hospital, Wonogiri, Central Java. Analysis was performed between the history of hypertension with severity and onset (<34 weeks and age ? 34 weeks gestational age). Data analysis was performed using SPSS software with univariate Chi-Square analysis.Results: A total of 44 medical record data were obtained in this study. A total of 20 patients (45.5%) had a history of hypertension and 24 (55.5%) patients had no history of hypertension. A total of 23 patients (52.3%) were diagnosed with severe preeclampsia and 21 patients (47.7%) were diagnosed with preeclampsia. Based on statistical analysis, it was found that there was no significant correlation between the history of hypertension and the severity of preeclampsia (p=0.741; OR (CI 95%): 0,818 (0,249 – 2,690)) and onset (p=0.88; OR (CI 95%): 1,133 (0,222 – 5,788)).Conclusion: There is no relationship between history of hypertension with the severity and onset of preeclampsia. Further studies with larger populations are needed to analyze the relationship between history of hypertension and preeclampsia.Keywords: blood pressure, cardiovascular disease, hypertension, onset, preeclampsia.